Role of kinesiophobia on pain, disability and quality of life in people suffering from chronic musculoskeletal pain: a systematic review - Luque-Suarez, Alejandro; Martinez-Calderon, Javier; Falla, Deborah (British journal of sports medicine, 2019)
Objective(1) To explore the level of association between kinesiophobia and pain, disability and quality of life in people with chronic musculoskeletal pain (CMP) detected via cross-sectional analysis and (2) to analyse the prognostic value of kinesiophobia on pain, disability and quality of life in this population detected via longitudinal analyses.DesignA systematic review of the literature including an appraisal of the risk of bias using the adapted Newcastle Ottawa Scale. A synthesis of the evidence was carried out.Data sourcesAn electronic search of PubMed, AMED, CINAHL, PsycINFO, PubPsych and grey literature was undertaken from inception to July 2017.Eligibility criteria for selecting studiesObservational studies exploring the role of kinesiophobia (measured with the Tampa Scale for Kinesiophobia) on pain, disability and quality of life in people with CMP.ResultsSixty-three articles (mostly cross-sectional) (total sample=10 726) were included. We found strong evidence for an association between a greater degree of kinesiophobia and greater levels of pain intensity and disability and moderate evidence between a greater degree of kinesiophobia and higher levels of pain severity and low quality of life. A greater degree of kinesiophobia predicts the progression of disability overtime, with moderate evidence. A greater degree of kinesiophobia also predicts greater levels of pain severity and low levels of quality of life at 6 months, but with limited evidence. Kinesiophobia does not predict changes in pain intensity.Summary/conclusionsThe results of this review encourage clinicians to consider kinesiophobia in their preliminary assessment. More longitudinal studies are needed, as most of the included studies were cross-sectional in nature.Trial registration numberCRD42016042641.